Information System for Optimization of 3 Kilograms Elpiji Gas Distribution Using the Least Cost Method (Case Study in PT. Hidayat Energi Putratama) - Albar, Moh. Ali; Baiq Rokyatul Jannah; Afwani, Royana (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
PT. Hidayat Energi Putratama is a 3 kilograms elpiji gas distribution agent that distributes elpiji gas to the base which then forms the base and will distribute to the retailer. Currently the calculation of distribution costs at PT. Hidayat Energi Putratama has not implemented an information system that can manage the calculation of distribution costs and the costs incurred are not optimal, so a system is needed to calculate distribution costs. The purpose of this research is to design an information system optimization of the distribution of 3 kilograms elpiji gas at PT. Hidayat Energi Putratama uses the least cost method that can perform calculations to help companies find out where the 3 kilograms elpiji gas should be distributed so that the costs incurred are kept to a minimum. From the results of research and calculations using the least cost method, the results obtained that the cost generated by the system is Rp. 1,120,600 less than the original cost incurred by the company of Rp. 1,500,000 so it can be said that the cost generated by using the least cost method is optimal. System testing is done by black box testing, theoretical calculations, and Mean Opinion Score (MOS) testing. The results of black box testing and theoretical calculations show that the system is running well and correctly. In the MOS test conducted on 30 respondents, the average result was 4.28 on a scale of 1 to 5. These results indicate that users are satisfied with the system built.